Narratives of sanitation: Motivating toilet use in India. Issue 111 (May 2020) - Leong, Ching
Abstract: One of the largest gaps between policy intent and actual public behavior lies in the area of sanitation. Despite well-established health benefits as well as intense government efforts, there remains a continued preference for open defecation (OD) in India. Previously vaunted participatory efforts such as Community Led Total Sanitation (CLTS) have also had limited empirical success. We explore this puzzle in Andhra Pradesh (AP) where large investments in latrines have been accompanied by low take-up rates. A survey of 300 residents reveals that the majority of latrine users are highly satisfied with the experience of using latrines, while the majority of non-users are highly dissatisfied with OD. At the same time, we find little or no resource impediment to the adoption of latrines. To explain these highly paradoxical findings, we conducted a quantitative investigation into the narratives of sanitation and find two key themes; the first describes a "technology society" with discourses on health, modernity and infrastructure; the second a "green society" with discourses on traditions, closeness with nature and practical conduct, which provides a strong defensible narrative for OD. Understanding these competing worldviews of the environment provides policy makers with a good premise for motivating latrine use as India urbanizes. It also explains the failure of CLTS methods which rely on "shame" and "disgust" to motivate long term behavioral change.